(X-5)(X-6)=56

Simple and best practice solution for (X-5)(X-6)=56 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X-5)(X-6)=56 equation:


Simplifying
(X + -5)(X + -6) = 56

Reorder the terms:
(-5 + X)(X + -6) = 56

Reorder the terms:
(-5 + X)(-6 + X) = 56

Multiply (-5 + X) * (-6 + X)
(-5(-6 + X) + X(-6 + X)) = 56
((-6 * -5 + X * -5) + X(-6 + X)) = 56
((30 + -5X) + X(-6 + X)) = 56
(30 + -5X + (-6 * X + X * X)) = 56
(30 + -5X + (-6X + X2)) = 56

Combine like terms: -5X + -6X = -11X
(30 + -11X + X2) = 56

Solving
30 + -11X + X2 = 56

Solving for variable 'X'.

Reorder the terms:
30 + -56 + -11X + X2 = 56 + -56

Combine like terms: 30 + -56 = -26
-26 + -11X + X2 = 56 + -56

Combine like terms: 56 + -56 = 0
-26 + -11X + X2 = 0

Factor a trinomial.
(-2 + -1X)(13 + -1X) = 0

Subproblem 1

Set the factor '(-2 + -1X)' equal to zero and attempt to solve: Simplifying -2 + -1X = 0 Solving -2 + -1X = 0 Move all terms containing X to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1X = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1X = 0 + 2 -1X = 0 + 2 Combine like terms: 0 + 2 = 2 -1X = 2 Divide each side by '-1'. X = -2 Simplifying X = -2

Subproblem 2

Set the factor '(13 + -1X)' equal to zero and attempt to solve: Simplifying 13 + -1X = 0 Solving 13 + -1X = 0 Move all terms containing X to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -1X = 0 + -13 Combine like terms: 13 + -13 = 0 0 + -1X = 0 + -13 -1X = 0 + -13 Combine like terms: 0 + -13 = -13 -1X = -13 Divide each side by '-1'. X = 13 Simplifying X = 13

Solution

X = {-2, 13}

See similar equations:

| 5x^4/10 | | 1000x^2-100x=0 | | 6x+2y+3y=11 | | (D^4+4D^2)y=96x^2 | | 2x11/4=13 | | (5.6x+2)(5.6x-2)= | | 25x^2+9y^2-18y-216=0 | | (0.6x-1.28)(18x+8)= | | 72=4x-12 | | 2m(n+3)-m(2n+1)= | | 2e^x/8e^-x | | X+0.6x=250y | | -5x+10=14+(4+x) | | g+7f=16 | | 12=3*x | | 4x^2+x=44 | | 9x+-9y=27 | | f(x)=10x-18 | | 4x^2+x-44=0 | | 50-(30+80)= | | u-v+6u-3v= | | (3x-4)(x-20)=3x(x-9)-3 | | 2-3(7x+9)=6 | | 5n^2+n-5=0 | | N+4=3n+16 | | -5t^2+40t+20= | | 0.2r-1.3r+0.6=-0.9+3.6 | | 19/2/3 | | 2/3/18 | | 2k+2=-13+3k | | X+0.6x+0.03x=500 | | 1/5-1/6z=7/6 |

Equations solver categories